Derivation Languages of Graph Grammars - Flick, Nils Erik (Electronic Communications of the EASST, 2013)
We investigate sequential derivation languages associated with graph grammars, as a loose generalisation of free-labeled Petri nets and Szilard languages. The grammars are used to output strings of rule labels, and the applicability of a special rule determines the acceptance of a preceding derivation. Due to the great power of such grammars, this family of languages is quite large and endowed with many closure properties. All derivation languages are decidable in nondeterministic polynomial time and space O(n log n), by simulation of the graph grammar on a Turing machine.